The development of broad-spectrum antiviral medical countermeasures to treat viral hemorrhagic fevers caused by natural or weaponized virus infections - Mark R. Hickman; David L. Saunders; Catherine A. Bigger; Christopher D. Kane; Patrick L. Iversen (Public Library of Science (PLoS), 2022)
The Joint Program Executive Office for Chemical, Biological, Radiological, and Nuclear Defense (JPEO-CBRND) began development of a broad-spectrum antiviral countermeasure against deliberate use of high-consequence viral hemorrhagic fevers (VHFs) in 2016. The effort featured comprehensive preclinical research, including laboratory testing and rapid advancement of lead molecules into nonhuman primate (NHP) models of Ebola virus disease (EVD). Remdesivir (GS-5734, Veklury, Gilead Sciences) was the first small molecule therapeutic to successfully emerge from this effort. Remdesivir is an inhibitor of RNA-dependent RNA polymerase, a viral enzyme that is essential for viral replication. Its robust potency and broad-spectrum antiviral activity against certain RNA viruses including Ebola virus and Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) led to its clinical evaluation in randomized, controlled trials (RCTs) in human patients during the 2018 EVD outbreak in the Democratic Republic of the Congo (DRC) and the ongoing Coronavirus Disease 2019 (COVID-19) pandemic today. Remdesivir was recently approved by the US Food and Drug Administration (FDA) for the treatment of COVID-19 requiring hospitalization. Substantial gaps remain in improving the outcomes of acute viral infections for patients afflicted with both EVD and COVID-19, including how to increase therapeutic breadth and strategies for the prevention and treatment of severe disease. Combination therapy that joins therapeutics with complimentary mechanisms of action appear promising, both preclinically and in RCTs. Importantly, significant programmatic challenges endure pertaining to a clear drug and biological product development pathway for therapeutics targeting biodefense and emerging pathogens when human efficacy studies are not ethical or feasible. For example, remdesivir's clinical development was facilitated by outbreaks of Ebola and SARS-CoV-2; as such, the development pathway employed for remdesivir is likely to be the exception rather than the rule. The current regulatory licensure pathway for therapeutics targeting rare, weaponizable VHF agents is likely to require use of FDA's established Animal Rule (21 CFR 314.600-650 for drugs; 21 CFR 601.90-95 for biologics). The FDA may grant marketing approval based on adequate and well-controlled animal efficacy studies when the results of those studies establish that the drug is safe and likely to produce clinical benefit in humans. In practical terms, this is anticipated to include a series of rigorous, well-documented, animal challenge studies, to include aerosol challenge, combined with human safety data. While small clinical studies against naturally occurring, high-consequence pathogens are typically performed where possible, approval for the therapeutics currently under development against biodefense pathogens will likely require the Animal Rule pathway utilizing studies in NHPs. We review the development of remdesivir as illustrative of the effort that will be needed to field future therapeutics against highly lethal, infectious agents. Author summary Development of medical countermeasures (MCMs) to treat and prevent viral infections with highly lethal filoviruses, such as Ebola virus (EBOV) and Marburg virus (MARV) is very difficult. Recently, US Food and Drug Administration (FDA)-approved vaccines and therapeutics for disease caused by EBOV and Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infections were obtained using the standard regulatory framework to address the new products' safety and efficacy profile with randomized clinical trials. Clinical trials were feasible as sufficient numbers of patients were available due to the large scale outbreaks with both Ebola and SARS-CoV-2. However, the opportunity to conduct human studies against emerging viral pathogens is relatively rare, and effectively impossible for high-consequence pathogens likely to be used in biowarfare and bioterrorism, such as the filoviruses. The alternative regulatory pathway for development of new drugs targeting biodefense pathogens that cannot be conducted when human efficacy studies are not ethical and field trials are not feasible is through the FDA's Animal Rule. In this review, we highlight how remdesivir's preclinical development path, based upon the Animal Rule for an EVD indication, was leveraged to support its ultimate regulatory approval as an antiviral agent for the treatment of Coronavirus Disease 2019 (COVID-19). The preclinical and clinical development of remdesivir for both SARS-CoV-2 and filovirus treatment including evidence from Animal Rule and clinical studies is also reviewed. The challenges associated with employing the Animal Rule for development of multiple biodefense therapeutics against numerous and distinct viral biothreats within Biosafety Level 4 are discussed. The issues of developing pharmaceuticals for weaponized viruses are also examined, along with a proposed pathway for drug study and approval to meet FDA requirements.